The registration of trade mark and the impact towards the firms' performance / Nordrul Safini Muhtar - Muhtar, Nordrul Safini (2007)
The objective or purpose of this study is to determine whether there is an impact or not before and after the registration of trade mark. Trade marks is also one of the intangible assets that include in balance sheet. Trade marks is one of the long-term assets. It is resources that also used to generate operating revenue for more than one period. To analyze the impact of the regisfration of trade marks, this study using 40 firms which have been listed in Bursa Malaysia and registered their frade marks. The based years are from 1991 to 2006 which is 14 years. From that period, which year the finn registered more their trade marks. For example AMWAY, this firms registered many trade marks on 1997, so the market capitalization can be used as before and after are 1996 as before and 2007 as after. The sample data are 40 market capitalizations before and 40 firms' after the registration of their trade marks. The objective of this study is to the registration of trade marks and the impact towards the firms' performance. The statistical test conducted by SPSS to examine the significant. There some previous study that concluded that there is positive impact before and after the registration of trade marks. There are also some researchers that argue that statement, because they found negative impact before and after the registration of trade mark. This study also can be used by investor as their guideline to know the impact of registration to the firms' performance.